Settlement of Bad Credit with Mortgage Guarantee at the Pintu Air Credit Cooperative Savings and Loans Cooperative, Kupang Branch - Adoe, Chicy La Viescha; Hedewata, Agustinus; Mauritsius, Darius (Indonesian Journal of Economic & Management Sciences, 2023)
There are many bad credit problems that occur in every cooperative. Here the author is interested in researching the Settlement of Bad Credit with Guarantee of Mortgage Rights where the Credit Savings and Loans Cooperative is located at the Water Gate Kupang Branch, and here the author takes 2 (two) problem formulations, namely the first, how to resolve bad credit with guarantee of mortgage rights in the Cooperative The Pintu Air Credit Cooperative Savings and Loans, Kupang Branch, and secondly, what are the obstacles experienced in resolving bad credit with mortgage rights at the Kupang Branch of the Pintu Air Credit Cooperative Savings and Loans. The research method uses qualitative research, using empirical research. The location of the research carried out was at the Pintu Air Credit Cooperative Savings and Loans Cooperative, Kupang Branch on Jalan Perintis Independen 3, Kelapa Lima Village, Kelapa Lima District, Kupang City. Primary data and secondary data are two types of data collected